Aphaniotis ornata (Ornate Shrub Lizard) - Muhammad Aini, Ujang; Hadimar, .; Sánchez, K.L.; Maiwald, M.J.; Das, Indraneil (Society for the Study of Amphibians and Reptiles, 2021)
New record for the agamid lizard Aphaniotis ornata for Kalimantan Barat is presented.